Epidemiological and Molecular Aspects on Cholera - Ramamurthy, T.; Bhattacharya, S.K.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Though cholera is an ancient disease, its perennial occurrence in several parts of the world has attracted many researches to find ways and means to combat the disease. The prevailing seventh pandemic cholera is dominating since 1961, but the dimension of the disease has taken several silhouettes, as the genetic structure and functions of the Vibrio cholerae has changed to a great extent. Several recent studies have shown that transformation of the pathogen at the molecular level has ameliorated several cholera outbreaks and epidemics of with successive new clones of V. cholerae. This comprehensive compilation, written by eminent international researchers reviews the epidemiology of cholera in Africa, Asia, Russia and Latin Americas. The other chapters contributed by acclaimed authors cover various aspects on evolution, polysaccaharide biosynthesis, SXT element, integrons, small molecule signalling systems, flagellar synthesis, filamentous phages, pathogenic role of proteases and hemolysin, and other putative virulence factors. In addition, ecology of V. cholerae and management of cholera were also discussed in detail. This book will be good source of information to all researchers with interests in infectious diseases, microbiology and molecular biology.
Keywords: Medicine; Infectious diseases; Microbiology; Medicine & Public Health; Infectious Diseases; Microbiology; Electronic books